Business continuity audit assessment: accounting and analytical aspect (Revista de Investigaciones Universidad del Quindío, 2022)
The financial stability of commercial organizations in the conditions of crisis phenomena demonstrated by the market economy is decreased. This increases the urgency in search and application of the most effective models developed for audit and diagnostics of economic activity of economic subjects. This study is dedicated to the analysis of business continuity audit assessment, especially accounting, and analytical aspects. To meet the study’s aim, an interview with employees of several departments of the refinery is conducted. Besides, general scientific methods, including descriptive and observational, are employed. Given the results, the business continuity assessment is less subjective than a management interview designed to confirm or deny the intention to continue operations uninterrupted for the foreseeable future.
Keywords: audit; business continuity; accounting and analytical information; control procedures